Modern Marketing Instruments in the Advertising Campaign - Galushka Kristina О.; Davydov Denys S. (Bìznes Inform, 2020)
The article considers topical issues of specifics of both marketing and advertising campaigns. The research is aimed at generalizing the methodical and practical aspects of the process of managing marketing instruments in the enterprise. Based on the information obtained from scientific sources, the efficiency of each instrument is evaluated using the method of observation and abstraction, as well as the method of comparative analysis. Different levels of strategy and basic instruments at each level are considered. In addition, key axioms that companies may face in the market when promoting goods and working with consumers have been identified. The need for a model of brand growth for the potential of the enterprise, which is conditioned by the importance of brands as intangible assets for effective competition and as a tool to create an efficient marketing campaign, is substantiated. The analysis also looked at the customer’s path from the search for a product to the acquisition of loyalty, as well as the most efficient modern marketing instruments at every stage. According to the results of analysis of the advertising market in Ukraine with the help of the All-Ukrainian Advertising Coalition, the media advertising market tends to increase volume, especially in the context of e-commerce and television. The main indicators of the efficiency of marketing campaigns to identify the subsequent direction for improving their activities are analyzed. The digital instruments have a number of capabilities and threats to the company when implementing any marketing campaign in the digital space that must be considered to minimize possible failures when launching a campaign.